2023
DOI: 10.3390/su15043511
|View full text |Cite
|
Sign up to set email alerts
|

Eating Sturgeon: An Endangered Delicacy

Abstract: Since ancient times, sturgeon species have been valued for their rich nutritional qualities, which are crucial for human health today. They are linked with gastronomic delicacy and offer economic benefits, especially for the caviar industry. Today aquaculture produces more farmed and hybrid species due to rapidly declining wild sturgeon populations. Sturgeon diversification through processing can yield fingerlings, stocking material, meat or caviar. Because of its variety, sturgeon flesh includes highly digest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Additionally, the oen 1 : 1 ratio of ionic liquid to metal salt to isolate these transition metal MILs leads to a high consumption of metal salts, which is not ideal with many of these metals being endangered elements. 31 The lanthanide series represents a unique class of metals to probe the desired trends for PET glycolysis. The ionic radius and Lewis acidity subtly change across the series, 32 allowing for an understanding of how Lewis acidity and metal ion size impacts PET depolymerization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the oen 1 : 1 ratio of ionic liquid to metal salt to isolate these transition metal MILs leads to a high consumption of metal salts, which is not ideal with many of these metals being endangered elements. 31 The lanthanide series represents a unique class of metals to probe the desired trends for PET glycolysis. The ionic radius and Lewis acidity subtly change across the series, 32 allowing for an understanding of how Lewis acidity and metal ion size impacts PET depolymerization.…”
Section: Introductionmentioning
confidence: 99%
“…The ionic radius and Lewis acidity subtly change across the series, 32 allowing for an understanding of how Lewis acidity and metal ion size impacts PET depolymerization. Additionally, lanthanide metals can allow a wide range of coordination environments, 31 in which the ratio of IL to metal ion can be varied. While there are a few reports of lanthanide metal-containing MILs for luminescence and nuclear waste separation, [33][34][35] none have been used for catalytic depolymerization of polymers.…”
Section: Introductionmentioning
confidence: 99%
“…15 Raposo et al studies indicated that sturgeon meat as a byproduct of caviar was not effectively utilized. 16 Our previous studies have focused on the exploration of the flavor of steamed sturgeon meat, and these results showed that umami and saltiness were the characteristic flavors of steamed sturgeon meat. However, these studies had focused on volatile flavor-active compounds, and changes in oral processing behavior of sturgeon meat, 17,18 with limited research conducted on nonvolatile flavor substances.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In the past decade, China’s sturgeon production has increased dramatically . Raposo et al studies indicated that sturgeon meat as a byproduct of caviar was not effectively utilized . Our previous studies have focused on the exploration of the flavor of steamed sturgeon meat, and these results showed that umami and saltiness were the characteristic flavors of steamed sturgeon meat.…”
Section: Introductionmentioning
confidence: 99%
“…Water interacts with delicate and often water-sensitive substrates, which increases treatment risks, while multiple misting applications (especially when treating large-scale objects) increase treatment time and costs. Moreover, Funori and Isinglass are products from the seaweed and sturgeon farming industries, that have begun to increasingly raise environmental and sustainability concerns [6]. High-density sturgeon farming operations often require significant amounts of water and are energy-intensive.…”
Section: Introductionmentioning
confidence: 99%